The Effect Of Leadership Style On Employee Compliance At The Dairi Regency Education Office - Adi Saputra R. Purba; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
The purpose of this study is to find out and analyze the influence of Leadership Style on Employee Compliance at the Dairi Regency Education Office. This research was carried out at the Dairi Regency Education Office. The type of research is quantitative associative. The sample in this study is 96 employees with ASN and honorary status at the Dairi Regency Education Office. The sampling technique in this study used the entire population of 45 people. The results of the study show that Leadership Style has a significant influence on Employee Compliance as shown by T-Statistic values of 2.737 > 1.678 and P Values of 0.009 < 0.05. This shows that improvements in Leadership Style can improve Employee Compliance at the Dairi Regency Education Office.